2012
DOI: 10.1287/mksc.1120.0737
|View full text |Cite
|
Sign up to set email alerts
|

Firm Innovation and the Ratchet Effect Among Consumer Packaged Goods Firms

Abstract: W e consider how public firms influence their stock market valuations by timing the introduction of innovative new products. Our focus is on innovation ratchet strategy-firms timing the introduction of innovations in order to demonstrate an improvement in the number of introductions over time. We document that public firms use an innovation ratchet strategy more often than do private firms and that the stock market rewards public firms for doing so. These rewards from the stock market, however, come at the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 58 publications
(57 reference statements)
0
39
0
Order By: Relevance
“…IDEX ASA located in Norway is found to have a higher patent intensity and R&D intensity, which is affected by the lower revenue. This might be because a firm with a high patent intensity often delays introductions and thus reduces potential revenue (Moorman, Wies, Mizik, & Spencer, 2012). In these two variables, these countries are not similarly characterized with respect to their R&D subsidy intensity (z h ) level.…”
Section: Tlmentioning
confidence: 99%
“…IDEX ASA located in Norway is found to have a higher patent intensity and R&D intensity, which is affected by the lower revenue. This might be because a firm with a high patent intensity often delays introductions and thus reduces potential revenue (Moorman, Wies, Mizik, & Spencer, 2012). In these two variables, these countries are not similarly characterized with respect to their R&D subsidy intensity (z h ) level.…”
Section: Tlmentioning
confidence: 99%
“…Particularly for public firms, top managers face widespread pressure from numerous stakeholders, and managers are expected to focus on investment that may create considerable short-term performance that would induce shareholders or potential investors to obtain substantial stock market returns [4,5]. Thus, with the increase of R&D intensity, the symbiotic tangible rewards, threats, deadlines, and competitive pressure diminish the intrinsic motivation of employees [60].…”
Section: Moderating Effect Of Randd Intensitymentioning
confidence: 99%
“…Given the significance of innovation, firms expect to understand the elements that determine incentives to innovate, especially for public firms because of their more complex internal and external environment [2,3]. Compared with a private firm, "myopic stock market incentives" propel managers to cut R&D expenditures and prefer projects with short-term and less risky returns that are favored easily by shareholders and potential investors [4,5]. Thus, when improvements in R&D expenditure encounter various restrictions, public firms transfer the perspective from tangible to intangible focus and discover that innovation culture may be a new avenue for improving innovation output [6].…”
Section: Introductionmentioning
confidence: 99%
“…Oligopolists may engage in "planned obsolescence" whereby they produce goods with uneconomically short useful lives, forcing customers to make otherwise unnecessary repeat purchases (Bulow, 1986). And Moorman et al (2012) found evidence some firms withhold innovative new products from the market for strategic reasons.…”
Section: Introductionmentioning
confidence: 99%